Creative Youth Against Unemployment: Strengthening Community-Based Social and Entrepreneurial Skills in Bone Regency, South Sulawesi - Asrijal, Andi; Zulkifli , Zulkifli; Indrawati, Ajeng R (Socious Journal, 2025)
This study aims to analyze the effectiveness of the Community Empowerment Program (PKM) "Creative Youth Anti-Unemployment" in improving the social skills and entrepreneurial capacity of community-based youth in Bone Regency, South Sulawesi. A descriptive qualitative approach was used with 30 research subjects, consisting of 22 youth program participants, 3 community leaders, 3 training facilitators, and 2 supporting partners from MSMEs and the local government, selected through purposive sampling. Data collection techniques included Focus Group Discussions, in-depth interviews, and field observations. Data analysis was conducted using the Miles-Huberman model through the stages of reduction, presentation, and drawing conclusions. The results show that the community plays a significant role in developing participants' social skills, including communication, leadership, and teamwork. Practice-based training and mentoring improve entrepreneurial capacity, product design, financial management, and business marketing skills. The integration between the community and training encourages participants' readiness to start independent businesses and reduces the risk of unemployment. The PKM program successfully fosters a resilient, creative, and proactive entrepreneurial mindset and strengthens social networks that support business sustainability. These findings confirm that community-based youth empowerment is an effective strategy for economic independence and sustainable social capacity development.